Implementation of Mediation as an Unique Step in Resolving Banking Business Disputes Sharia in Religious Courts - Zainal Abidin Pakpahan (Garuda Prestasi Nusantara Consulting, 2022)
Mediation steps that are rarely carried out in sharia economic business problems are contained in the Al-Quran and Hadith which have been relied upon to be implemented in sharia banking, so that sharia business problems are now starting to enter a unique renewal phase which is the basis for fast and low-cost processes as the wheels of running the economy. because Islamic banks in their operations are still limited by Bank Indonesia regulations and applicable laws, for example the mudharabah principle, the Bai' Salam principle, the Wadi'ah principle, the Musyarakah principle, and the leasing principle (Ijarah). Islamic banks in their wheel of rotation are certainly inseparable from problems both internally and externally through financing with customers even though they are solely based on the principle of profit sharing. Keyword:Mediation, Disputes, Business, Sharia Banking.